On the geometry of cross surface of one class of tensor supporting elements spaces with straightline base - Bliznikienė, I. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. В. Близникене. О геометрии секущей поверхности одного класса пространств тензорных опорных элементов с линейчатой базой I. Bliznikienė. Apie vienos klasės tenzorinių atraminių elementų su tiesialinijine baze kertamojo paviršiaus geometriją